2009
DOI: 10.1159/000214851
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory and Molecular Characteristics of Recessive von Willebrand Disease Type 2C (2A Subtype IIC) of Variable Severity due to Homozygous or Double Heterozygous Mutations in the D1 and D2 Domains

Abstract: The detection of even tiny amounts of von Willebrand factor (VWF):antigen after desmopressin treatment or in hidden sites like platelets allows the differentiation between patients with recessive von Willebrand disease (VWD) type 3, severe type 1, and 2C (2A subtype IIC). Recessive VWD 2C of various severity displays a characteristic multimeric pattern with pronounced dimer band, absence of triplet structure and lack of large multimers not due to increased proteolysis. Recessive VWD type 2C (2A subtype IIC) is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
(43 reference statements)
1
3
0
Order By: Relevance
“…As shown in ▶ Figure 1, besides the additional mutations identified by NGS, the characteristic mutation distribution across VWF was preserved in each VWD type: in type 3 VWD, the mutations were scattered throughout VWF; in severe type 1 VWD, the profile was similar, but the absence of mutations in the regions coding for the A1, A2, D' and D3 domains was evident; in type 2N VWD, a mutation cluster in the region coding for the D1, D' and D3 domains was detected; in types 2A, 2B and 2M VWD, the mutation spreading was notable, but a mutation cluster in the regions coding for the A1 domain emerged. These findings are in line with previous reports (5,(31)(32)(33)(34).…”
Section: Discussionsupporting
confidence: 93%
“…As shown in ▶ Figure 1, besides the additional mutations identified by NGS, the characteristic mutation distribution across VWF was preserved in each VWD type: in type 3 VWD, the mutations were scattered throughout VWF; in severe type 1 VWD, the profile was similar, but the absence of mutations in the regions coding for the A1, A2, D' and D3 domains was evident; in type 2N VWD, a mutation cluster in the region coding for the D1, D' and D3 domains was detected; in types 2A, 2B and 2M VWD, the mutation spreading was notable, but a mutation cluster in the regions coding for the A1 domain emerged. These findings are in line with previous reports (5,(31)(32)(33)(34).…”
Section: Discussionsupporting
confidence: 93%
“…Recently, it has been demonstrated that part of severe type 1 and type 2A VWD are also inherited in an autosomal recessive manner (1). Pathogenic variants responsible for dominant type 2A are predominantly located in A2, A1 and D3 domains, while mutations located in the propeptide or C-terminal cystine knot domain could cause recessive type 2A (46)(47)(48). Here we presented What is known about this topic?…”
Section: Vwfpp (%)mentioning
confidence: 89%
“…The p.C295S substitution found in our patient, which also replaces a cystein in the D1 domain, is the first IIC mutation in exon 8. Previous mutations were described in exons 11, 12, 14 and 15 [38,39]. The IIC variant is a recessive phenotype, and the case of patient 25 is an example of the diagnostic difficulties (or overlap between phenotypes) faced by physicians taking care of patients with severe von Willebrand disease.…”
Section: Discussionmentioning
confidence: 99%